Unveiling Phonological Patterns: An Introductory Exploration - Dwitalestari Dwitalestari; Rosa Anjani; Miftahul Jannah; Dea Saharani; Yani lubis (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
Phonology is one of the main subjects that make up the study of language, which is called the scientific study of the structure of language. One way to understand the meaning of language is to compare it to other parts of language. Basically, phonology is a science that studies the sound structure of language, as opposed to the study of sentence structure (grammar), word structure (morphology), and language variation over time (history). This definition is too simplistic and unnecessary. The research method used in writing this article is library research, this method is to search for reference materials through previous scientific works, in the form of journals, theses, books, etc. According to Seewoester (2009), humor is the manipulation of language at the linguistic level. Creating confusion and ambiguity with your words can influence many reactions from your audience, including laughter and confusion. Be careful with your language. Some strategies for creating humor in comic situations use sound effects such as sound substitution, deletion, addition, deductive pairing, metathesis, and sound compatibility.